Ibrutinib-Associated Cardiac Tamponade with Concurrent Antiplatelet Therapy - Jennifer L. Miatech; John H. Hughes; Dillon K. McCarty; M. Patrick Stagg (Case Reports in Hematology)
Ibrutinib is approved for the first-line treatment of chronic lymphocytic leukemia (CLL). A well-known side effect of ibrutinib therapy is increased bleeding risk, which ranges from mild mucocutaneous bleeding to rarely life-threatening hemorrhage. The increased bleeding tendency associated with ibrutinib is thought to be related to its effect on several platelet signaling pathways, which can be exacerbated in the setting of concurrent antiplatelet or anticoagulant therapy. We present an 82-year-old male with CLL on ibrutinib and concurrent antiplatelet therapy who developed cardiac tamponade due to a hemorrhagic pericardial effusion requiring emergent placement of a pericardial window. This case further highlights the risk of major bleeding in patients treated with ibrutinib and concurrent antiplatelet therapy.